The Implementation of Modeling Technique on Social Skills of People With Mental Psychotic Disability - Cep Yoga Firmansyah; Dorang Luhpuri; Rosyikin Sukanda (Politeknik Kesejahteraan Sosial Bandung, 2017)
Social skills are not the capacity that can be easily mastered by persons with mental disabilities; they endeavor to master and/-or regain control of these capacities. Having 2 persons with mental disabilities as case studies, the objective of this study is to improve social skills of those persons with disabilities in more stable mental condition. This research uses a quantitative approach with a single subject experimental research design utilizing multiple baseline cross subject model; two persons with mental disabilities having similar characteristics and behavior became respondents of the study. Data analysis has been conducted by means of graph making, descriptive statistics, and visual inspection. Furthermore, the research uses face validity for its test validation and inter-rater reliability (kappa coefficient) in the reliability test. The study shows that 4 (four) aspects of social skills of the two respondents has been increasing since the intervention started. The behavioral improvement can be seen in the aspects of their communication, people-to-people interaction, ways to cooperate, and motivation for doing daily activities. The post-intervention’s (A2) measurement indicated that there was a decrease of behavioral frequency even though the number is still above the prior-intervention phase (A1). The decline was allegedly triggered by changes of activities of the two respondents.